Respuesta :

Answer:

2x-y/3

Step-by-step explanation:

Answer:

2x -y = 2

Step-by-step explanation:

If you want it in standard form this is what it would look like 2x-y=2

first, the easiest thing to do is multiply the whole thing by 3, since the fractions denominators are the same.

you should get:

2x -y = 2

standard form formula = Ax + By = C

so luckily, the equation above we just solved is already in standard form after multiplying everything by 3

remember that in standard form, A cannot be negative, and we can't have any fractions in the equation